Pyramiding vs leverage in corporate groups: International evidence - Faccio, Mara; Lang, Larry HP; Young, Leslie (Journal of International Business Studies, 2010)
Among firms listed in Western Europe and East Asia, when creditor protection is strong, the controlling shareholder trades off retaining control in bad states through pyramiding against retaining the upside in good states via leverage. This result might arise because the controlling shareholder uses both leverage and pyramiding to expand control of resources, but in different circumstances since they have different outcomes under downside shocks. When creditor protection is weak, the controlling shareholder no longer prefers pyramiding in bad states, because creditors will not be able to seize the firm in bad states. Therefore pyramiding and leverage are used together.